ANALISIS SEGI EMPAT KEJAHATAN PADA KASUS PEMBUNUHAN MASSAL TERHADAP ANAK KANDUNG: STUDI LITERATUR - Selly Dwining Maulidina; Fani Oktaviani Agustin, Ririn Ida Royana, Mita Widyaningrum, Indah Rosdiyan, Tugimin Supriyadi (ADISAM PUBLISHER, 2025)
The quadrilateral of crime is a concept that describes the main factors that affect the occurrence of crime. This concept consists of four elements, namely victims, crimes, perpetrators and social reactions. This study aims to analyze the relationship of these four elements to the occurrence of crime and analyze the Crime Quadrilateral in the Case of mass Murder of Biological Children and how external factors such as social environment and economic conditions affect the dynamics of these elements. This research was conducted with a literature study. The form is in the form of selecting information sources through a review of the literature that has been used, with appropriate references and following the established format